2021
DOI: 10.1177/00027642211021623
|View full text |Cite
|
Sign up to set email alerts
|

Survey Data Quality in Analyzing Harmonized Indicators of Protest Behavior: A Survey Data Recycling Approach

Abstract: This article proposes a new approach to analyze protest participation measured in surveys of uneven quality. Because single international survey projects cover only a fraction of the world’s nations in specific periods, researchers increasingly turn to ex-post harmonization of different survey data sets not a priori designed as comparable. However, very few scholars systematically examine the impact of the survey data quality on substantive results. We argue that the variation in source data, especially deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Ex post survey harmonization is a useful approach to overcome limited coverage over periods and countries by creating a single data set that pools and adjusts variables from different surveys that were not designed to be compared in the first place (Granda & Blasczyk, 2016; Tomescu-Dubrow & Slomczynski, 2016). The SDR project has constructed a large data set that harmonizes the survey items about attending demonstrations and signing petitions from 19 international survey projects for 136 countries and territories from 1966 to 2013 (Slomczynski et al, 2016; Slomczynski et al, this issue). It is notable that the data set harmonizes regional surveys such as the Afrobarometer (AFB), Asian Barometer, and Latinobarometer, which cover historically underrepresented regions in protest research.…”
Section: Intersurvey Methodological Variability In Survey Data Harmon...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ex post survey harmonization is a useful approach to overcome limited coverage over periods and countries by creating a single data set that pools and adjusts variables from different surveys that were not designed to be compared in the first place (Granda & Blasczyk, 2016; Tomescu-Dubrow & Slomczynski, 2016). The SDR project has constructed a large data set that harmonizes the survey items about attending demonstrations and signing petitions from 19 international survey projects for 136 countries and territories from 1966 to 2013 (Slomczynski et al, 2016; Slomczynski et al, this issue). It is notable that the data set harmonizes regional surveys such as the Afrobarometer (AFB), Asian Barometer, and Latinobarometer, which cover historically underrepresented regions in protest research.…”
Section: Intersurvey Methodological Variability In Survey Data Harmon...mentioning
confidence: 99%
“…These harmonization and survey quality variables can be used as statistical controls in the multivariate analysis to account for methodological intersurvey variability (Kwak, 2020; Slomczynski & Tomescu-Dubrow, 2019). In their assessment of these measures, Slomczynski et al (2021) show that these measures account for at least 5% of the variation in past protest behavior and are not randomly distributed. It would seem to be important to control for these in analyses of these data.…”
Section: Intersurvey Methodological Variability In Survey Data Harmon...mentioning
confidence: 99%
See 1 more Smart Citation
“…We test for both the linear and quadratic forms, which have both received support in the literature. At the national survey level, we control for harmonization adjustments and survey quality, which are provided by the SDR data set and control for intersurvey variability reflecting artifacts of harmonization decisions and/or differences in survey quality (see also, Kwak, this issue; Slomczynski et al, this issue). Table 1 provides descriptive statistics for these variables.…”
Section: Constructing Survey Estimates Of Protest Participationmentioning
confidence: 99%
“…It uses an additive scale ranging from 0 to 3 that sums three dichotomous variables that capture whether the survey has: (1) nonunique records; (2) more than 5% of missing data on either age or gender; or (3) errors in respondent IDs, which is likely linked to errors in archiving or other survey management problems. Past work has shown that these errors can possibly lead to distorted empirical results (Slomczynski et al, this issue; Slomczynski, Powałko, et al, 2017; Zieliński et al, 2018). Seventeen percent of our source files had one or more of these problems.…”
Section: Constructing Survey Estimates Of Protest Participationmentioning
confidence: 99%